2021
DOI: 10.1016/j.sapharm.2020.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Management of human resources of a pharmacy department during the COVID-19 pandemic: Take-aways from the first wave

Abstract: The coronavirus disease 2019 (COVID-19) is the biggest public the world has seen in many years and poses new challenges and opportunities to healthcare systems. The new reality imposed by the pandemic requires a modification of practices to ensure the health and safety of patients and medical teams. The purpose of this article is to share the experiences of the pharmacy department of the Centre hospitalier de l’Université de Montréal (CHUM) in response to the COVID-19 pandemic. Seven of the most important issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 6 publications
0
40
0
1
Order By: Relevance
“…They also listed the disadvantages and challenges of working from home as: social isolation the need for new forms of management interference between personal and occupational life the cost of setting up home office facilities and the need for time management skills [ 41 ]. …”
Section: Discussionmentioning
confidence: 99%
“…They also listed the disadvantages and challenges of working from home as: social isolation the need for new forms of management interference between personal and occupational life the cost of setting up home office facilities and the need for time management skills [ 41 ]. …”
Section: Discussionmentioning
confidence: 99%
“…A Canadian study found that pharmacist were significantly more efficient validating prescriptions remotely from home, compared to centralised workstations at the hospital, proposed to be due to less distractions and interruptions. 35 Pharmacists also preferred remote working for their work-life balance, flexibility and stress reduction. 35 The drawbacks were cited as social isolation, conflicts between professional and private life, cost of setting up a home office, and the greater need for self-motivation and good time management.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Pharmacists also preferred remote working for their work-life balance, flexibility and stress reduction. 35 The drawbacks were cited as social isolation, conflicts between professional and private life, cost of setting up a home office, and the greater need for self-motivation and good time management. 35 Going forward, this study adds to the evidence of potential positive of reconsidering working environments, with the potential to alternate between remote working and on-site working to maximise the benefits and limit social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…In some countries (14), HPs reorganised their activities to limit their HR risks: roles were redistributed and non-pharmacist staff were used to assist in manufacturing units and answer the phone (15). Another study reported HPs encouraging work from home and physical distancing (16).…”
Section: Discussionmentioning
confidence: 99%